Analysis of Teachers’ Understanding Level, Needs, and Difficulties in Identifying Children with Special Needs in Inclusve School in Surakarta - Dian Atnantomi Wiliyanto (Intelektual Pustaka Media Utama, 2017)
This research was aimed to determine teachers’ understanding level of identification concept, needs, and difficulties in implementing the identification of children with special needs in inclusive school. It was a descriptive research with 40 special teachers as the subject taken by using purposive random sampling in 11 inclusive school in Surakarta. Data was cllected through interview and questionnaire. Data was analyzed by using percentage quantitative descriptive. Result of the research showed that: (1) teachers’ understanding level of the identification of children with special needs was strongly uncomprehend (37%), uncomprehend (23%), and less comprehend (18%); (2) teachers’ needs of the identification of children with special needs mostly need training program and digital identificatio instrument development, (3) problems found in the field about identification of children with special needs are identification instrument standardize, difficulty in applying identification steps, low competence of non-special-education teacher about identification and in detecting similar characteristics of children with special needs.